Cytotoxic and genotoxic evaluation of different synthetic amorphous silica nanomaterials in the V79 cell line. (September 2016) - Guichard, Y; Fontana, C; Chavinier, E; Terzetti, F; Gaté, L; Binet, S; Darne, C
The nature of occupational risks and hazards in industries that produce or use synthetic amorphous silica (SAS) nanoparticles is still under discussion. Manufactured SAS occur in amorphous form and can be divided into two main types according to the production process, namely, pyrogenic silica (powder) and precipitated silica (powder, gel or colloid). The physical and chemical properties of SAS may vary in terms of particle size, surface area, agglomeration state or purity, and differences in their toxicity potential might therefore be expected. The aim of this study was to compare the cytotoxicity and genotoxicity of representative manufactured SAS samples in Chinese hamster lung fibroblasts (V79 cells). Five samples from industrial SAS producers were evaluated, that is, two pyrogenic SAS powders (with primary particle sizes of 20 nm and 25/70 nm), one precipitated SAS powder (20 nm) and two precipitated SAS colloids (15 and 40/80 nm). V79 cell cultures were treated with different concentrations of SAS pre-dispersed in bovine serum albumin –water medium. Pyr (pyrogenic) 20, Pre (precipitated) 20 and Col (colloid) 15 significantly decreased the cell viability after 24 h of exposure, whilst Pyr 25/70 and Col 40/80 had negligible effects. The cytotoxicity of Pyr 20, Pre 20 and Col 15 was revealed by the induction of apoptosis, and Pyr 20 and Col 15 also produced DNA damage. However, none of the SAS samples generated intracellular reactive oxidative species, micronuclei or genomic mutations in V79 cells after 24 h of exposure. Overall, the results of this study show that pyrogenic, precipitated and colloidal manufactured SAS of around 20 nm primary particle size can produce significant cytotoxic and genotoxic effects in V79 cells. In contrast, the coarser-grained pyrogenic and colloid SAS (approximately 50 nm) yielded negligible toxicity, despite having been manufactured by same processes as their finer-grained equivalents. To explain these differences, the influence of particle agglomeration and oxidative species formation is discussed.